2020
DOI: 10.1007/s11930-020-00262-8
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Desire and Fantasies in the LGBT+ Community: a Focus on Bisexuals, Transgender, and Other Shades of the Rainbow

Abstract: Purpose of Review The purpose of this review is to summarize the current knowledge on sexual desire expressions, sexual orientation, and identity in understudied groups inside the LGBT+ community. Recent Findings Sexual desire and related problems have unique expressions in LGBT+ people which influence their sexual health. Emerging sex-positive approaches might be powerful and prominent tools to provide support and education on behalf of safer sex practices and marginalized sexualities. The importance of deepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 60 publications
(78 reference statements)
1
14
0
Order By: Relevance
“…People who were practicing Mindfulness reached higher scores on the Hurlbert Index of Sexual Fantasy (HISF) scale, meaning they had more positive attitudes towards sexual fantasies. Consistent with other authors, this is an indicator of good sexual health [55], higher levels of sexual desire [56] and constitutes a good indicator of sexual functioning in older women [57]. The initial research made by Sánchez-Sánchez, Luciano and Barnes-Holmes (2009) showed that the effort to suppress an exciting thought brings this more strongly by a rebound effect [58].…”
Section: Discussionsupporting
confidence: 75%
“…People who were practicing Mindfulness reached higher scores on the Hurlbert Index of Sexual Fantasy (HISF) scale, meaning they had more positive attitudes towards sexual fantasies. Consistent with other authors, this is an indicator of good sexual health [55], higher levels of sexual desire [56] and constitutes a good indicator of sexual functioning in older women [57]. The initial research made by Sánchez-Sánchez, Luciano and Barnes-Holmes (2009) showed that the effort to suppress an exciting thought brings this more strongly by a rebound effect [58].…”
Section: Discussionsupporting
confidence: 75%
“…For example, some transfeminine people/trans women may refer to their genitals as a clit to reflect their gender identity (Bauer & Hammond, 2015; Doorduin & van Berlo, 2014). As with every group though, it is important to remember that the trans community experiences sexuality in diverse ways and that people’s particular sexual behaviors vary widely (Bauer et al., 2013; Klein & Gorzalka, 2009; Nimbi et al., 2020; Williams et al., 2016).…”
Section: Sexual Behaviorsmentioning
confidence: 99%
“…There are many examples of these sex-biases in research, which have led to the stereotyping of phenomena, wrong associations and misinterpretations of data. For example, gender and sexual orientation scripts have guided research on sexual desire and fantasies for years (Nimbi et al, 2020a(Nimbi et al, , 2020b, and literature on HIV/AIDS still focuses primarily on gay men and anal sex (Burnes et al, 2017). A sex-positive approach should change the style of communication by using more updated, inclusive terms and producing more realistic scientific evidence.…”
Section: Researchmentioning
confidence: 99%